Beyond Prohibition: A Proposal for an International Treaty on Parental Readiness to Safeguard Child Welfare - Maximillian Kenas Tarmidi (Notaire, 2026)
Globalization has accelerated the erosion of traditional social structures, creating a vacuum where the welfare of children is increasingly precarious. This new landscape presents dual threats: the normalization of "free sex" and unstructured relationships which can lead to unstable family environments, and the reactionary persistence of child marriage, often a consequence of socioeconomic instability amplified by global pressures. Both phenomena critically endanger a child's fundamental right to a secure and nurturing upbringing. Current international human rights law, however, remains largely reactive, addressing harm only after it has occurred. This research posits a radical but necessary evolution of human rights doctrine: a proactive framework legally mandating parental readiness. It argues that for the "welfare of the child" to be a meaningful legal standard, it must be guaranteed before conception and birth. The author proposes an international treaty, or a new protocol to the Convention on the Rights of the Child (CRC), that establishes clear, universal prerequisites for legal marriage and parenthood. These prerequisites would be twofold: a minimum level of educational attainment to ensure cognitive and emotional maturity, and a verifiable minimum threshold of financial stability to guarantee the provision of a child's basic needs. This is not a limitation on freedom, but a fulfillment of a collective duty to ensure that every child is born into a world of opportunity, not disadvantage. This framework reframes child welfare as the paramount human right, a right that society has the obligation to proactively secure.